Health itinerary-related survival of children under-five with severe malaria or bloodstream infection, DR Congo. - Bieke Tack; Daniel Vita; José Nketo; Naomie Wasolua; Nathalie Ndengila; Natacha Herssens; Emmanuel Ntangu; Grace Kasidiko; Gaëlle Nkoji-Tunda; Marie-France Phoba; Justin Im; Hyon Jin Jeon; et al. (Public Library of Science (PLoS), 2023)
Background Prompt appropriate treatment reduces mortality of severe febrile illness in sub-Saharan Africa. We studied the health itinerary of children under-five admitted to the hospital with severe febrile illness in a setting endemic for Plasmodium falciparum (Pf) malaria and invasive non-typhoidal Salmonella infections, identified delaying factors and assessed their associations with in-hospital death. Methodology Health itinerary data of this cohort study were collected during 6 months by interviewing caretakers of children (>28 days - <5 years) admitted with suspected bloodstream infection to Kisantu district hospital, DR Congo. The cohort was followed until discharge to assess in-hospital death. Principal findings From 784 enrolled children, 36.1% were admitted >3 days after fever onset. This long health itinerary was more frequent in children with bacterial bloodstream infection (52.9% (63/119)) than in children with severe Pf malaria (31.0% (97/313)). Long health itinerary was associated with in-hospital death (OR = 2.1, p = 0.007) and two thirds of deaths occurred during the first 3 days of admission. Case fatality was higher in bloodstream infection (22.8% (26/114)) compared to severe Pf malaria (2.6%, 8/309). Bloodstream infections were mainly (74.8% (89/119)) caused by non-typhoidal Salmonella. Bloodstream infections occurred in 20/43 children who died in-hospital before possible enrolment and non-typhoidal Salmonella caused 16 out of these 20 bloodstream infections. Delaying factors associated with in-hospital death were consulting traditional, private and/or multiple providers, rural residence, prehospital intravenous therapy, and prehospital overnight stays. Use of antibiotics reserved for hospital use, intravenous therapy and prehospital overnight stays were most frequent in the private sector. Conclusions Long health itineraries delayed appropriate treatment of bloodstream infections in children under-five and were associated with increased in-hospital mortality. Non-typhoidal Salmonella were the main cause of bloodstream infection and had high case fatality. Trial registration NCT04289688.